Zoran Skoda
extended Jordanian twist

Borel algebra, Jordanian twist exp(Hln(1+ξE))exp(H\otimes ln (1+\xi E))

Ogievetsky

[H,E]=E[H, E] = E

Frobenius algebra, add A i,B iA_i,B_i, extended Jordanian twist

parameters α i+β i=1\alpha_i + \beta_i =1

[H,A i]=α iA i[H,A_i] = \alpha_i A_i, [H,B i]=β iB i[H,B_i] = \beta_i B_i;

[E,A i]=[E,B j]=0[E,A_i] = [E,B_j] = 0

[A i,B j]=δ ijγ iE[A_i,B_j] = \delta_{i j}\gamma_i E

can have several pairs

ϕ=exp(AB(1+ξE) γ)exp(Hln(1+ξE)\phi = exp(A \otimes B(1+\xi E)^{-\gamma}) exp(H \otimes ln (1+\xi E)

Kulish Lyakhovski Mudrov 1995 or so

σ=ln(1+ξE)\sigma = ln (1+\xi E)

Δ ϕ(H)=He σ+1H\Delta_{\phi}(H) = H\otimes e^{-\sigma}+ 1\otimes H

lightcone basis kappa Mink H=M +H = M_{+-}

E=P +=P 0+P 3E=P_+ = P_0+P_3

M +aM_{+a}, P aP_a

Created on November 19, 2013 at 01:39:04. See the history of this page for a list of all contributions to it.